HLA-B gene methylation and expression in Behçet's syndrome: a potential role of epigenetics in the pathogenesis - Özkılınç Önen, Merve; Everest, Elif; Demirci, Turna; Köprülü Şen, Pelinsu; Kızıltepe Kısakesen, Esra; Özgüler, Yeşim; Esatoğlu, Sinem Nihal; Seyahi, Emire; Tahir Turanlı, Eda (Clinical and Experimental Rheumatology, 2023)
The HLA-B51 locus has the strongest association with Behçet's syndrome (BS). The presence of a CpG island in the HLA-B gene led us to examine the role of epigenetic regulation in BS.HLA-B51 genotyping was performed via sequence-specific PCR in 15 index familial BS cases, 17 affected relatives, 26 unaffected relatives, 46 sporadic BS cases, and 41 healthy controls. HLA-B methylation level was determined using the Zymo OneStep qMethyl kit, and HLA-B51 mRNA level was assessed by quantitative real-time PCR in 14 index familial BS cases, 15 affected relatives, 15 unaffected relatives, 11 sporadic BS cases, and 10 healthy controls.HLA-B51 carrier ratio was 13/15 in index familial cases, 13/17 in affected relatives, 22/26 in unaffected relatives, 8/25 in healthy controls, and 35/47 in sporadic BS cases. HLA-B51 expression level in HLA-B51+ BS cases was 2.2-fold higher than in their unaffected relatives (p=0.0149) and 1.3-fold higher than in healthy controls (p=0.0188), while sporadic BS cases had a 2.7-fold higher level than healthy controls (p=0.0487). HLA-B promoter methylation was significantly lower in HLA-B51+ familial BS cases than in unaffected relatives (0.4-fold, p=0.01), affected relatives (0.36-fold, p=0.0219), and healthy controls (0.34-fold, p=0.0371) and slightly lower in HLA-B51+ sporadic BS cases than in healthy controls (0.71-fold, p=0.2347). There was an inverse correlation between HLA-B promoter methylation and HLA-B51 expression in HLA-B51+ sporadic BS cases (p=0.0164).This study indicates epigenetic involvement associated with the HLA-B51 locus in BS, both in familial and sporadic cases. Further studies with larger sample sizes are needed to confirm our results.
Keywords: Male; Adult; Heredity; Behcet Syndrome; DNA Methylation; Middle Aged; Epigenesis, Genetic; Young Adult; Phenotype; HLA-B Antigens; Case-Control Studies; HLA-B51 Antigen; Humans; Female; Genetic Predisposition to Disease; CpG Islands; RNA, Messenger